(untitled) (Ciudades, 2018)
Ciudad Pegaso was promoted by the Empresa Nacional de Autocamiones (ENASA), linked to the Instituto Nacional de Industria, to provide housing for its employees. It is an early example of an industrial district created by the urban policies of the time (sketches 1949, first phase 1956, second phase 1960). There, the Falangist ideas of the “Ciudad del Movimiento” (an organic and gated city in which the class struggle is overcome by their juxtaposition in the same space) come together, and on the other hand, the tendency of the regime in favor of segregation of the working masses in suburban neighborhoods as a form of social control, come together.